2010
DOI: 10.1387/ijdb.093055ac
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of hematopoietic development in Xenopus and zebrafish

Abstract: Blood development has been highly conserved during evolution. Hematopoietic cells in amphibian and fish embryos, as in mammalian embryos, emerge and progressively differentiate in several locations. Hematopoiesis, including of the immune system, is similar in the amphibian, Xenopus, to mammals and the embryos are ideal for tissue transplantation and lineage labelling experiments, which have enabled the elucidation of the distinct origins of embryonic and adult hematopoietic cells, as well as their migration pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
76
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 87 publications
3
76
0
1
Order By: Relevance
“…The staining of the cement gland may be an artifact, as an occasional nonspecific staining of it was found earlier [18]. Presumptive myeloid blood cells were concentrated at these stages in the middle of ventral area of embryo [25]. We saw the Xvent-2 protein staining in this area too (Figure 5(c)).…”
Section: Spatial Patterning Of the Xvent-2 Protein Insupporting
confidence: 71%
See 1 more Smart Citation
“…The staining of the cement gland may be an artifact, as an occasional nonspecific staining of it was found earlier [18]. Presumptive myeloid blood cells were concentrated at these stages in the middle of ventral area of embryo [25]. We saw the Xvent-2 protein staining in this area too (Figure 5(c)).…”
Section: Spatial Patterning Of the Xvent-2 Protein Insupporting
confidence: 71%
“…The mRNA was found along the edge of the neural tube [3,5,6,9] along the edge of the presumptive forebrain [13], in the presumptive eyes, bronchial arch, tail bud [3][4][5][6] somites [3] and in the areas of the mieloid ventral blood island [4,5,25]. The Xvent-2 mRNA was absent in the cement gland [3][4][5][6].…”
Section: Spatial Patterning Of the Xvent-2 Protein Inmentioning
confidence: 99%
“…Thus, the DLP proximal to the pronephros originates from medial blastomeres and gives rise to the DA encompassing the trunk, the site where HSCs emerge in the Xenopus embryo. By contrast, the DLP distal to the pronephros originates from more ventral blastomeres and gives rise to the tail artery, which does not produce HSCs (Mills et al, 1999;Ciau-Uitz et al, 2010a). Additionally, we and others have previously shown that the DLP, immediately adjacent to the ventral edge of the developing somites, contains cells co-expressing haematopoietic and endothelial genes; and that cells from the DLP migrate to the RESEARCH ARTICLE The adult haemangioblast GRN midline to coalesce and form the DA and, eventually, give rise to haemogenic endothelium and HSCs (Cleaver and Krieg, 1998;Ciau-Uitz et al, 2000;Walmsley et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Recent tissue imaging and molecular analysis have revealed that HSCs are generated from specialised endothelial cells that acquire blood potential, the haemogenic endothelium, and are localised in the ventral wall of the single medial dorsal aorta (DA) (reviewed by Medvinsky et al, 2011). The intimate association between the DA and HSC ontogeny is conserved throughout vertebrate evolution, including in model organisms such as the zebrafish and Xenopus (reviewed by Ciau-Uitz et al, 2010a). In addition, the signalling events involved in the specification of the DA also play crucial roles in HSC generation Ciau-Uitz et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…Primitive myeloid cells are specified in two waves in Xenopus, the first one from the embryonic hemangioblast as early as the end of gastrulation at stage 13 [runx1 (35), cebpa, spib, and mpo expression profiles submitted directly to Xenbase (36) by A.C.-U. ], and the second one from posterior ventral tissues around stage 30 in close association with the primitive blood islands (37). Embryonic hemangioblasts are first exposed to BMP ligands at the end of gastrulation by stage 13 (38).…”
mentioning
confidence: 99%